Collaboration Network Model of HIV/AIDS Prevention and Control: Case Study in Subang District, Indonesia - Raharja, Sam'un Jaja; Akhmad, Dede (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
This study was conducted due to the increasing trend of people living with Human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/AIDS) (HIV/AIDS) in Subang Regency, West Java Province. This phenomenon was marked by high population mobility. Thus, this study aims to analyze the network model for HIV/AIDS prevention and control in Subang Regency. In this study, a networking approach by collaboration was adopted using six dimensions, namely, governance, administration, organizational autonomy, mutuality, norms and leadership. A qualitative approach is applied to explain a dataset which was a collection of observation and in - depth interview and supported by secondary data from relevant informants who are involved in preventing and reducing HIV/AIDS in Subang Regency. These informants were the actors who represent government agents and non-government organizations. Result showed that all dimensions of collaboration occur on an iterative, cyclical and dynamic process. However, on a practical approach, this model is implemented on a linear and causality basis and can explain a system towards problem-solving and new values forming.